CADIK SAMUDRA BOROBUDUR : Jenius Lokal Nusantara - Primadi Tabrani (Jurnal Budaya Nusantara, 2014)
Dugout canoe is from prehistory. It develops to become outrigger canoe: catamaran, one out- rigger and two outrigger. Then it is equipped with sails. After that came the plank built outrigger. There are still many mystery about the development of dugout canoeinto plank built outrigger. When and where does it appear? What about its dispersal so that outrigger canoe is every where in Austronesia? The ocean outrigger vessel as seen in the Borobudur relief, is a Nusantara local jenius. It is for voyages between islands, trading, passenger, war, even ocean liner. With this kind of ship Sriwijaya and Majapahit became great maritime kingdom, not only in South East Asia, but also in Asia and in the world as well.With this kind of ship, Nusantara are able to wander to the Pacific, the Indian and the Atlantic, all three Ocean in the world. At those times, Nusantara is the only people that are able to do that.